Oxidation of magnesium alloys at elevated temperatures in air: A review. (November 2016) - Tan, Qiyang; Atrens, Andrej; Mo, Ning; Zhang, Ming-Xing
Highlights: The oxidation behaviours of Mg alloys from low to high temperatures are reviewed. Characteristics of MgO during oxidation is discussed. Mechanisms of Mg oxidation is presented. Effect of various alloying elements is analysed. Abstract: This paper reviews (i) the oxidation of Mg alloys at elevated temperatures in air; (ii) the influence of alloying elements on the oxidation of Mg alloys; and (iii) the progress in the development of oxidation-resistant Mg alloys. Low oxidation rates have been shown by Mg alloys containing the alloying elements, Ca, Be and rare earth elements. However, these alloying elements may also decrease mechanical properties, such as ductility.